2012
DOI: 10.4238/2012.november.28.2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma human mammaglobin mRNA associated with poor outcome in patients with breast cancer

Abstract: ABSTRACT. Different treatment outcomes and prognoses in patients with breast cancer can be observed with similar clinical predictors; this is because the biology of breast cancer is complex and heterogenous, involving multiple unknown contributing factors. We looked for plasma human mammaglobin (hMAM) mRNA by RT-PCR in 82 Korean patients with breast cancer to determine if there is an association Plasma mammaglobin mRNA and prognostic factors between the presence of plasma hMAM mRNA in these patients and known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…Increased mammaglobin expression in breast cancer was associated with clinical and biologic features characteristic of a less aggressive phenotype as expression was significantly higher in estrogen receptor (ER)-positive tumors [23,24]. A small number of reports has shown that expression of mammaglobin affects disease (or event) free survival (DFS or EFS) and OS, in agreement with numerous studies showing that mammaglobin is one of the most promising markers for breast cancer diagnosis [25][26][27][28][29][30]. However, the relationship between mammaglobin and OS, a gold standard primary end point to evaluate the outcome of any drug, biologic, intervention or procedure that is assessed in oncologic clinical trials [31], is controversial among researchers.…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…Increased mammaglobin expression in breast cancer was associated with clinical and biologic features characteristic of a less aggressive phenotype as expression was significantly higher in estrogen receptor (ER)-positive tumors [23,24]. A small number of reports has shown that expression of mammaglobin affects disease (or event) free survival (DFS or EFS) and OS, in agreement with numerous studies showing that mammaglobin is one of the most promising markers for breast cancer diagnosis [25][26][27][28][29][30]. However, the relationship between mammaglobin and OS, a gold standard primary end point to evaluate the outcome of any drug, biologic, intervention or procedure that is assessed in oncologic clinical trials [31], is controversial among researchers.…”
Section: Introductionsupporting
confidence: 65%
“…The percentage of mammaglobin expression in peripheral blood ranged 8.0% to 48.8% in breast cancer patients. Four studies included sample obtained from patients with metastatic breast cancer [25][26][27]29].…”
Section: Study Characteristics and Patient Populationsmentioning
confidence: 99%
See 3 more Smart Citations